HUKUM LINGKUNGAN DALAM PERSPEKTIF ISLAM (Studi Kasus atas Fenomena Pemanasan Global (Global Warming)) - Suansar Khatib (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2015)
Environmental law in Islamic Perspective (Case Study of Global WarmingPhenomena). The develpment of advance technology has caused a people to do furtherexploration, this optimitic thinking reach it peak in 19 century, where the science andtechnology become a key to solve the problem of the people. This thought is supported by thefrench philosoper Auguste Comte (1798-1857), he mentioned that the scientific era as thepositif era the peak and the last of history. But this optimistic thought is not all truth as theresult of development of advance technology it can caused a negative impact as well aspositif. Beside the development of all sectors which defenitely would be a profit to humankind, but another problem has come to appear in the issue of environment such as the waste ofindustrial impact, acid rain, cavity of ozon, the melting of ice in antarctic which raising thelevel of sea water, and the impact of glass which claimed to have caused the instability ofclimate and temperature that could destroy the life of human and others. Presently, the humanfaced a new crisis, at this point we came to know that how many forest has been destroyed?To what extend the impact of environment due to the waste caused by technology from theexploitation which endangered the human life it self, this is happened due to the act ofirresponsible human that forgotten the social order of society